Penerapan Strategi Mastery Learning Menggunakan Media Visual pada Pembelajaran Fisika Peserta Didik Kelas XI MAN I Padang - Andria, Luciana (Natural Science: Jurnal Penelitian Bidang IPA dan Pendidikan IPA, 2017)
The purpose of this research to know the implementation of learning mastery strategy in using visual media to give the student score are better than conventional learning. The design of this research was quasy experiment with randomized control group only design. The population of this research were all of student’s class XI - XI  MAN 1 Padang period 2016-2017. In determining experimental class and control class used cluster random sampling technique. The data was analyzed hyphotesis testing and t-test because the data was normal and the group of data has homogen varians.based on the research finding, it can be conduded that experimental class is more increase than control class. In spiritual aspect, experiment class got three criteria very good and one criteria good whereas control class got four criteria good. In social aspect, experiment class got one criteria very good and three criteria good where as control class got four criteria good. In attitude aspect, experiment class got four criteria very good whereas control class got three criteria very good and one criteria good. In cognitive aspect, experiment class still achieve mean score 79,59 where as the mean score of control class was 75,75. Based on analyzed of t-test in post test got t-calculate=1,90, where as t-table = 1,67, it means that  was rejected and  was accepted. The result of the research showed that the implementation of learning mastery strategy using visual media was better and in crease the score of student physic than conventional learning.